Domino Reaction of 2,2-Dihydroxyindene-1,3-dione with Aromatic Amines: Efficient Synthesis of Isochromeno[4,3-b]indol-5(11H)-one Derivatives - Meng, Xiao-Yan; Sun, Mu-Yan; Zhao, Fu-Jie; Dang, Yi-Jing; Jiang, Bo; Tu, Shu-Jiang (Synthesis, 2014)
An efficient approach to 16 examples of polyfunctionalized isochromeno[4,3-b]indol-5(1H)-one derivatives, obtained in 60–85% yield and with excellent regioselectivity, has been developed through a domino reaction of 2,2-dihydroxyindene-1,3-dione with aromatic amines under microwave irradiation. The atom- and step-economy and scope make this reaction a powerful tool for assembling polyheterocyclic scaffolds of general chemical and biomedical interest.
Keywords: domino reactions; heterocycles; cyclizations; regioselectivity; isochromeno[4,3-b]indol-5(11H)-one; 2,2-dihydroxyindene-1,3-dione; aromatic amines